Effect of Post Weld Heat Treatment on Tensile Strength of ASTM A36 Welded Joints: Application on Hull Vessel Material - M. Uswah Pawara; Alamsyah Alamsyah; Muhammad Syarif; Faisal Mahmuddin; Harifuddin Harifuddin (International Journal of Marine Engineering Innovation and Research, 2023)
In fact, in the welding process, there are many problems that arise. Such as cracking caused by excessive stress Residual stress can result in a decrease in the mechanical properties of a material such as brittle fracture, fatigue, and cracking. The purpose of this study was to determine the comparison of tensile strength in ASTM plate welded joints A36 with variations of single vee butt and single bevel butt and knowing the comparison of the effects ofpost-weldd heat treatment on welded joints with variations of single v butt and single bevel butt joints. The method used in this research is experimental. The results of the data obtained in this study The value of the tensile strength of the Single Bevel Butt joint without the influence of Heat Treatment is 153.87 MPa, the tensile strength of the Single Vee Butt joint without the influence of Heat Treatment is 161.75 MPa and the tensile strength of the seam Single Bevel Butt with the effect of Heat Treatment is 196,65 MPa. The tensile strength of the Single Vee Butt seam with the effect of Heat Treatment is 173,36 MPa.